Investigation of Insulin-Like Growth Factor 2 mRNA Binding Protein 2 Gene Polymorphisms in Type 2 Diabetes Patients - Duygu Yolal Ertural; Ümit Çınkır; Nurcan Aras (Genel Tıp Dergisi)

(untitled)
Background/Aims: Type 2 diabetes (T2D) whose prevalance differs in different populations is a multifactorial disease. T2D is describes a group of clinical syndromes resulting from glucose metabolism disorders triggered by genetic or environmental factors. Insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) gene participates in insulin signaling pathway and is involved in insulin secretion. SNPs in one of these genes, IGF2BP2 gene (rs1470579 and rs4402960), have been reported to partially increase the risk of type II diabetes. The aim of this study was to investigate in a Turkish population identified associations of IGF2BP2 variants rs4402960 and rs1470579 with T2D.Methods: We genotyped two SNPs of IGF2BP2 gene, rs1470579 and rs4402960 in 100 healthy individuals and 100 patients. DNA isolation was performed on peripheral blood samples from patients and healthy groups. The molecular analysis of rs1470579 and rs4402960 polymorphisms of IGF2BP2 gene of each individual was performed by using Real-Time PCR (Applied Biosystems) method. Relationships of genotypes and alleles frequency of IGF2BP2 polymorphisms and T2D were examined by "Chi-square" or "Likelihood ratio" tests.Results: As a result of the genotype and allele distributions; there was association between type II diabetes patients and control group for IGF2BP2 rs1470579 (A/C) gene polymorphism (p=0.0123). The frequency of AC genotype in patients is more than the control group. However, there was no statistically significant difference genotype distribution between the type 2 diabetes patients and control group for IGF2BP2 rs4402960 (G/T) gene polymorphisms. There was no association between the patients and the control group for TT and GG+GT genotype distribution (p=0.8847). Conclusions: The results showed that the IGF2BP2 gene rs1470579 and rs4402960 polymorphisms were associated with T2D in a Turkish population (OR = 2.002, 95% CI 1.170–3.426, p < 0.05; OR = 1.879, 95% CI 1.110–3.182, p< 0.05). This is the first study between IGF2BP2 gene polymorphisms and type II diabetes in Turkish population.Keywords: IGF2BP2, T2D, Polymorphism